Electromagnetic studies along the Neseno-Irzhavets—Abramivka profile (Southern Slope of the Dnieper-Donets trough) - Kushnir, A.N.; Burakhovich, T.K.; Ilyenko, V.A.; Dzhaoshvili, V.B. (Reports of the National Academy of Sciences of Ukraine, 2018)
The simultaneous MT/MV studies were carried out along the Neseno-Irzhavets—Abramivka profile to study the deep structure of the lithosphere and to search for electrical conductivity anomalies that may be caused by the fracturing of the rocks, through which the fluids migrate and possibly create hydrocarbon deposits. The described new modern experimental electromagnetic parameters should detail the Kirovograd electrical conductivity anomaly and become the basis for the three-dimensional model construction in such complex geological environment as the uneven-aged structure junction. The described experimental MT/MV observations confirm the deep anomalous structures that were investigated in the previous years.